THE MANAGEMENT OF COMPLEMENTARY THERAPIES TO STABILIZE GLUCOSE LEVELS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Putri, Moudy Muhaiminurrohima; Pujiyanto, Pujiyanto (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Diabetes Mellitus (DM) is a chronic disease and a global public health challenge. The aim of this study is to review the most commonly used complementary therapies to control glycemic in patients with type 2 DM. The research contributes to the field of diabetes management by systematically reviewing and evaluating complementary therapies that are frequently employed for diabetes management. The literature searches are structured through online databases including Pubmed, Cochrane, and Science Direct. The population in this study was individuals with uncomplicated type 2 diabetes mellitus who were >18 years of age, the interventions were complementary and alternative therapies, the study types were RCT and Quasi Experimental, and the result was controlled lipid levels. A total of 12 articles were obtained that met the inclusion criteria. The results of the literature review through PRISMA showed that the majority of the articles were published in English and English. The majority of articles were randomized controlled trials (RCTs) that evaluated the efficacy of complementary therapies in reducing blood glucose, insulin resistance, and oxidative status in type 2 diabetic patients. In addition, this review can highlight gaps in the current literature, paving the way for future research initiatives aimed at exploring the effectiveness, safety, and mechanisms of action of various complementary approaches in diabetes management, thereby facilitating informed decision-making in patient care.